Enhanced nattokinase production by Bacillus subtilis from glycerol and okara: optimization of culture medium via response surface methodology - Duan, Yaling; Du, WanTing; Xu, Yang; Guo, Gege; Liu, Zhaoxing; Hao, Ning (Frontiers in Microbiology, 2025)
IntroductionNattokinase is an alkaline serine protease with potent thrombolytic activity. Due to its safety profile, low cost, and ease of oral administration, it has gained significant attention for therapeutic applications. To meet the demand for cost-effective production of nattokinase via fermentation, this study utilized renewable biomass resources—glycerol and okara—as raw materials for nattokinase production.MethodsA metabolic pathway for efficient glycerol utilization in Bacillus subtilis 13,932 was engineered using genetic modifications. The co-expression of glpF and glpK significantly enhanced the strain’s ability to metabolize glycerol. Building upon this, fermentation conditions using glycerol as the carbon source and okara as the nitrogen source were optimized. A Box-Behnken Design was employed to determine the optimal medium composition. Additionally, fermentation parameters were further optimized through a single-factor experiment.ResultsThe optimal medium composition was determined to be: glycerol 23 g/L, okara 96 g/L, MgSO4⋅7H2O 0.8 g/L, and CaCl2 0.7 g/L, yielding a nattokinase activity of 8709.53 ± 103.45 IU/mL. Further optimization of fermentation parameters resulted in the highest nattokinase activity of 10576.28 ± 91.78 IU/mL under the following conditions: 37 °C, 200 rpm shaking speed, 7% inoculum, and an initial pH of 7.5.DiscussionThe genetic modifications enabling efficient glycerol metabolism in Bacillus subtilis 13,932, along with the optimized fermentation strategy using renewable resources, significantly improved nattokinase production. The high enzymatic activity achieved demonstrates the potential of this approach for cost-effective and sustainable nattokinase production.